Colorectal cancer screening for average‐risk adults: 2018 guideline update from the American Cancer Society. (30th May 2018) - Wolf, Andrew M.D.; Fontham, Elizabeth T.H.; Church, Timothy R.; Flowers, Christopher R.; Guerra, Carmen E.; LaMonte, Samuel J.; Etzioni, Ruth; McKenna, Matthew T.; Oeffinger, Kevin C.; Shih, Ya‐Chen Tina; Walter, Louise C.; Andrews, Kimberly S.; et al.
Abstract: In the United States, colorectal cancer (CRC) is the fourth most common cancer diagnosed among adults and the second leading cause of death from cancer. For this guideline update, the American Cancer Society (ACS) used an existing systematic evidence review of the CRC screening literature and microsimulation modeling analyses, including a new evaluation of the age to begin screening by race and sex and additional modeling that incorporates changes in US CRC incidence. Screening with any one of multiple options is associated with a significant reduction in CRC incidence through the detection and removal of adenomatous polyps and other precancerous lesions and with a reduction in mortality through incidence reduction and early detection of CRC. Results from modeling analyses identified efficient and model‐recommendable strategies that started screening at age 45 years. The ACS Guideline Development Group applied the Grades of Recommendations, Assessment, Development, and Evaluation (GRADE) criteria in developing and rating the recommendations. The ACS recommends that adults aged 45 years and older with an average risk of CRC undergo regular screening with either a high‐sensitivity stool‐based test or a structural (visual) examination, depending on patient preference and test availability. As a part of the screening process, all positive results on noncolonoscopy screening tests should be followed up with timely colonoscopy. The recommendation to begin screening at age 45 years is a qualified recommendation . The recommendation for regular screening in adults aged 50 years and older is a strong recommendation . The ACS recommends ( qualified recommendations ) that: 1) average‐risk adults in good health with a life expectancy of more than 10 years continue CRC screening through the age of 75 years; 2) clinicians individualize CRC screening decisions for individuals aged 76 through 85 years based on patient preferences, life expectancy, health status, and prior screening history; and 3) clinicians discourage individuals older than 85 years from continuing CRC screening. The options for CRC screening are: fecal immunochemical test annually; high‐sensitivity, guaiac‐based fecal occult blood test annually; multitarget stool DNA test every 3 years; colonoscopy every 10 years; computed tomography colonography every 5 years; and flexible sigmoidoscopy every 5 years.CA Cancer J Clin 2018;68:250–281 . ©2018 American Cancer Society .